Ramadan Fasting in Germany (17–18 h/Day): Effect on Cortisol and Brain-Derived Neurotrophic Factor in Association With Mood and Body Composition Parameters - Riat, Amin; Suwandi, Abdulhadi; Ghashang, Samaneh Khoshandam; Buettner, Manuela; Eljurnazi, Luqman; Grassl, Guntram A.; Gutenbrunner, Christoph; Nugraha, Boya (Frontiers in Nutrition, 2021)
Ramadan fasting (RF) is a type of diurnal intermittent fasting. Previous studies reported the benefits of RF in healthy subjects on mood and health related to quality of life (QoL). Cortisol and brain-derived neurotrophic factor (BDNF) have been shown to play a role in mood, body composition parameters, and health-related QoL. This study aimed at elucidating the mechanism of the benefit of RF, particularly cortisol and BNDF and their association with mood and QoL. Insulin growth factor-1 (IGF-1), interleukin (IL)-8, matrix metalloproteinase (MMP)-9, and myoglobin were determined. Thirty-four healthy men and women were recruited. Serum from peripheral venous blood samples was collected at five time points: 1 week before RF (T1); mid of RF (T2), last days of RF (T3), 1 week after RF (T4), and 1 month after RF (T5). The amounts of biological mediators in the serum samples were determined by enzyme-linked immunosorbent assay (ELISA) and Luminex assays. BDNF and cortisol significantly decreased at T3 (p < 0.05) and T4 (p < 0.001) compared to T1, respectively. It seems the benefits of RF for mood-related symptoms are mediated by different biological mediators, particularly cortisol and BDNF.